Strategizing continuous delivery in cloud : your easy-to-follow guide for implementing continuous delivery using modern cloud native technology /: your easy-to-follow guide for implementing continuous delivery using modern cloud native technology. (2023) - Bajpai, Garima; Schuetz, Thomas
No abstract available